2019
DOI: 10.3389/fimmu.2019.02738
|View full text |Cite
|
Sign up to set email alerts
|

Host Immune Responses and Immune Evasion Strategies in African Trypanosomiasis

Abstract: Parasites, including African trypanosomes, utilize several immune evasion strategies to ensure their survival and completion of their life cycles within their hosts. The defense factors activated by the host to resolve inflammation and restore homeostasis during active infection could be exploited and/or manipulated by the parasites in an attempt to ensure their survival and propagation. This often results in the parasites evading the host immune responses as well as the host sustaining some self-inflicted col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 146 publications
0
35
0
Order By: Relevance
“…However, the cellular and molecular adaptations that allow parasite tropism are still poorly understood. For many parasites, tropism to specific organs is an essential step of their life cycle, because the organs provide a niche for persistence, latency or dormancy, massive replication and/or growth, protection from the host immune responses, or differentiation into alternative stages essential for completion of the life cycle, among others ( Boyett and Hsieh, 2014 ; Fernandes and Andrews, 2012 ; Guérin and Striepen, 2020 ; Lima and Lodoen, 2019 ; Onyilagha and Uzonna, 2019 ; Prudêncio et al., 2006 ; Rénia and Goh, 2016 ; Silva Pereira et al., 2019 ; Venugopal et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the cellular and molecular adaptations that allow parasite tropism are still poorly understood. For many parasites, tropism to specific organs is an essential step of their life cycle, because the organs provide a niche for persistence, latency or dormancy, massive replication and/or growth, protection from the host immune responses, or differentiation into alternative stages essential for completion of the life cycle, among others ( Boyett and Hsieh, 2014 ; Fernandes and Andrews, 2012 ; Guérin and Striepen, 2020 ; Lima and Lodoen, 2019 ; Onyilagha and Uzonna, 2019 ; Prudêncio et al., 2006 ; Rénia and Goh, 2016 ; Silva Pereira et al., 2019 ; Venugopal et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental setting, we have previously shown that the human DTPa vaccine loses efficacy during active T. b. brucei infection. This observation could be explained by the multiple levels of immune suppression that are induced during active trypanosomosis [53][54][55][56]. In contrast, the study here provides data showing that the problem at hand is the active destruction of the functional host immune memory compartment.…”
Section: Discussionmentioning
confidence: 76%
“…Examination of bone marrow is of low yield in detecting trypanosomes [ 6 ], and bone marrow smear as a means of diagnosis is rare [ 9 , 10 ]. Polyclonal activation of B cells is a hallmark of HAT, resulting in elevated IgG and IgM levels, as well as false-positive antibodies for pathogens, and autoantibodies [ 11 ].…”
Section: Discussionmentioning
confidence: 99%